Changes in lower limb biomechanics across various stages of maturation and implications for ACL injury risk in female athletes: a systematic review - Ramachandran, A. K.; Pedley, J. S.; Moeskops, S.; Oliver, J. L.; Myer, G. D.; Lloyd, R. S. (Sports Medicine, 2024)
Key Points